CIB2, defective in isolated deafness, is key for auditory hair cell mechanotransduction and survival - Vincent Michel; Kevin T Booth; Pranav Patni; Matteo Cortese; Hela Azaiez; Amel Bahloul; Kimia Kahrizi; Ménélik Labbé; Alice Emptoz; Andrea Lelli; Julie Dégardin; Typhaine Dupont; et al. (EMBO Molecular Medicine)
Abstract Defects of CIB2, calcium‐ and integrin‐binding protein 2, have been reported to cause isolated deafness, DFNB48 and Usher syndrome type‐IJ, characterized by congenital profound deafness, balance defects and blindness. We report here two new nonsense mutations (pGln12* and pTyr110*) in CIB2 patients displaying nonsyndromic profound hearing loss, with no evidence of vestibular or retinal dysfunction. Also, the generated CIB2−/− mice display an early onset profound deafness and have normal balance and retinal functions. In these mice, the mechanoelectrical transduction currents are totally abolished in the auditory hair cells, whilst they remain unchanged in the vestibular hair cells. The hair bundle morphological abnormalities of CIB2−/− mice, unlike those of mice defective for the other five known USH1 proteins, begin only after birth and lead to regression of the stereocilia and rapid hair‐cell death. This essential role of CIB2 in mechanotransduction and cell survival that, we show, is restricted to the cochlea, probably accounts for the presence in CIB2−/− mice and CIB2 patients, unlike in Usher syndrome, of isolated hearing loss without balance and vision deficits.